Carbon-assisted catalyst pretreatment enables straightforward synthesis of high-density carbon nanotube forests. (November 2019) - Dee, Nicholas T.; Li, Jinjing; Orbaek White, Alvin; Jacob, Christine; Shi, Wenbo; Kidambi, Piran R.; Cui, Kehang; Zakharov, Dmitri N.; Janković, Nina Z.; Bedewy, Mostafa; Chazot, Cécile A.C.; Carpena-Núñez, Jennifer; et al.
Abstract: Despite extensive academic and commercial development, a comprehensive understanding of the principles necessary for high-yield production of carbon nanotubes (CNTs) is lacking, whether in oriented films, bulk powders, or other forms. In chemical vapor deposition growth of CNT films on substrates, trace contaminants of carbon, such as deposits on the reactor tube walls, are known to cause inconsistency in key production metrics, including CNT density and alignment. In this study, we show that trace exposure of the catalyst to carbon during initial heating of the catalyst film is a critical determinant of CNT yield, and this carbon exposure accelerates catalyst nanoparticle formation via film dewetting and increases the probability of CNT nucleation and the resultant density of the CNT population. By controlled exposure of the catalyst to a trace amount of carbon, we show up to a 4-fold increase in bulk mass density for a given forest height, an 8-fold increase in local CNT number density, and a 2-fold increase in the growth lifetime, relative to a reference condition. We discuss potential mechanisms to explain the role of carbon exposure on the probability of CNT nucleation from nanoparticle catalysts, supported by microscopy and gas analysis. Graphical abstract: Image 1